Kebijakan dan Peraturan Pemerintah, Gaya Kepemimpinan dan Kinerja Pegawai dalam Meningkatkan Produktivitas Usaha Kecil dan Menengah Indonesia: Government Policies and Regulations, Leadership Style and Employee Performance in Increasing Productivity of Indonesia’s Small and Medium Enterprises - Akmal Umar; Andi Adawiah; Abdul Halim Barkatullah; Ifrani Ifrani; Mahyuni Mahyuni; M Ali Amrin; Nur Ali Farisi (Society, 2022)
The performance and productivity of any enterprise is a contentious topic of discussion in development. This research looks at the performance of Small and Medium Enterprises (SMEs) and how they are regulated to increase company productivity. Specifically, the paper sought to establish how policies and regulations contribute to leadership tasks, loyalty, employee motivation and job performance, affecting a firm’s production capacity. Policies and Regulations are examined in this paper because to enhance the performance of Small and Medium-sized Enterprises, the government of Indonesia issued regulation No. 20/2008, Article 3 about Micro, Small and Medium Enterprises intending to support the growth and development of the economy since 99% of the country’s economy is support by SMEs which also employees 97% of the working population of the country, yet there is still limited research on policies in relation performance and Productivity of SMEs. Though policies are a fundamental component in business growth, it has been established that employee performance affects company productivity, affecting local employment rates. The sample population was taken from Indonesia’s Small and Medium Enterprises (SMEs) employees. The sample size was 250, and PLS software was applied to analyze the data. The study’s findings showed the leadership role’s significance concerning existing Policies and Regulations regarding SMEs. It was also revealed that motivational policies enable employees to go beyond expectations and show higher levels of job performance in their respective tasks, increasing productivity.